Semantic-Style Characteristics of Certain Color Defining Adjectives in The Modern Uzbek Language (Journal of Pedagogical Inventions and Practices, 2023)
This article presents opinions about the connotative meaning of adjectives denoting color. The article also provides information on the use of color adjectives and their analysis.